The undeciphered signs of Linear B interpretation and scribal practices - Judson, Anna P. 1989- (Cambridge classical studies, 2020)
Decades after Michael Ventris deciphered Linear B and showed that its language was Greek, nearly one-sixth of its syllabic signs' sound-values are still unknown. This book offers a new approach to establishing these undeciphered signs' possible values. Analysis of Linear B's structure and usage not only establishes these signs' most likely sound-values - providing the best possible basis for future decipherments - but also sheds light on the writing system as a whole. The undeciphered signs are also used to explore the evidence provided by palaeography for the chronology of the Linear B documents and the activities of the Mycenaean scribes. The conclusions presented in this book therefore deepen our understanding not only of the undeciphered signs but also of the Linear B writing system as a whole, the texts it was used to write, and the insight these documents bring us into the world of the Mycenaean palaces. A colour version of figures 5.1-5.4 of chapter 5 can be found under the 'Resources' tab